Effects of variables on natural convective heat transfer through V-corrugated vertical plates - Hasanuzzaman, M.; Saidur, Rahman; Ali, M.; Masjuki, Haji Hassan (International Journal of Mechanical and Materials Engineering, 2007)
Natural convection is an important mode of heat transfer. Natural convective heat transfer is a common phenomenon in most of the heat transfer cases. This paper presents the natural convective heat transfer and the effect of different variables on heat transfer in the square enclosure of two V-corrugated parallel vertical plates. An experiment has been performed to investigate the effect of mass flow rate of cooling water, input heat energy and inlet water temperature on natural convective heat transfer in the square enclosure of two V-corrugated parallel vertical plates. The air inside the V-corrugated parallel vertical plates was the main media to transfer heat from the hot V-corrugated plate to cold V-corrugated plate. Mass flow rate and the inlet temperature of cooling water are considered to vary the cold plate temperature. The increase in mass flow rate of water and the input heat energy increases the heat transfer rate. On the other hand, the decrease in inlet water temperature increases the heat transfer rate. So, there is an influence of different variables on natural convective heat transfer through V-corrugated vertical plates.